Penerapan Sanksi Tindakan terhadap Anak Pelaku Tindak Pidana Pencabulan - Putri, Citra Mutiara; Fardiansyah, Ahmad Irzal; Muhtadi, Muhtadi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Children who commit criminal offenses require a justice approach that prioritizes their rights and welfare. This study examines the legal basis and judicial considerations in imposing sanctions on children convicted of committing criminal acts of threats of violence forcing other children to commit obscene acts, based on Decision Number: 8/Pid.Sus-Anak/2024/PN.Gdt in the Pesawaran District Court. The objective is to analyze how judges apply legal, philosophical, and sociological considerations in sentencing child offenders while aligning with the principles of child protection law in Indonesia. This research uses a normative juridical approach with conceptual, statutory, and case study methods. Data were collected through literature review and analyzed using legal interpretation techniques, including grammatical, teleological, and restrictive interpretations. The findings indicate that judges apply sanctions in the form of rehabilitation measures rather than imprisonment, considering the child's young age (13 years) and the best interest of the child. Judicial considerations include ensuring the protection of children's rights under Law Number 11 of 2012 on the Juvenile Criminal Justice System and Law Number 17 of 2016 concerning Child Protection. The sanction imposed a one-year placement in a Child Special Guidance Institution (LPKS) reflects a restorative justice approach, aiming for rehabilitation and reintegration of the child into society while balancing the interests of victims and maintaining public legal order.